Genetic Diversity Patterns and Heterosis Prediction Based on SSRs and SNPs in Hybrid Parents of Pearl Millet. Issue 6 (18th October 2018) - Singh, Satbeer; Gupta, S. K.; Thudi, Mahendar; Das, Roma Rani; Vemula, Anilkumar; Garg, Vanika; Varshney, R. K.; Rathore, Abhishek; Pahuja, S. K.; Yadav, Dev Vart
Abstract : The present investigation was performed to assess genetic divergence and heterosis prediction in hybrid parents of pearl millet [ Pennisetum glaucum (L.) R Br.] using simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers. Using 56 SSR loci, 412 alleles were detected in 147 lines with an average of 7.36 alleles per locus, and 75, 007 SNP loci were detected in 117 lines. Both SSR‐ and SNP‐based clustering and structure analysis partitioned all maintainer (B) and restorer (R) lines into two clear‐cut separate groups, indicating the existence of two diverse gene pools, each representing the seed and restorer parents in pearl millet. Results of analysis of molecular variance and principal coordinate analysis also showed significant diversity between B and R lines. The correlation between parental genetic distances estimated based on SSRs and SNPs was high and significant ( r = 0.58, p <.01). Similar clustering pattern of hybrid parents was observed with both marker systems, although the cost of genotyping was 41% less with SNPs than with SSRs, and the ratio of loci detected with SNPs was much higher (1:364 SSR/SNP), hence the use of SNPs is indicated over SSRs for germplasm characterization. A set of 136 hybrids (including all B × B, R × R, and B × R crosses) generated crossing 17 hybrid parents (nine B lines and eight R lines) in half diallel (without reciprocal) fashion, and evaluation at two locations revealed that the correlation between genetic distance and better parent heterosis for grain yield was moderate, positive, and significant (with SSR, 0.33, p <.01; with SNP, 0.35, p <.01), hence both SSRs and SNPs were found comparable in results for heterosis prediction.